1)
3х-3<х-3 5х+15>2х+3
2х<0 3х>-12
х<0 х>-4
Потом чертишь числовую прямую на которой отмечаешь точку 0 и -4
ответ:х принадлежит (-4;0)
2)
{ 2(y-2) >= 3y+1
{ 5(y+1) <= 4y+3
Раскрываем скобки
{ 2y - 4 >= 3y + 1
{ 5y + 5 <= 4y + 3
Упрощаем
{ y <= -5
{ y <= -2
ответ: y = (-oo; -5]
3)
{ 3(2y-3) <= y+6
{ 4(3y+1) >= 5y-10
Раскрываем скобки
{ 6y - 9 <= y + 6
{ 12y + 4 >= 5y - 10
Упрощаем
{ 5y <= 15; y <= 3
{ 7y >= -14; y >= -2
ответ: y = [-2; 3]
4)
{ 2(3x+2) > 5(x-1)
{ 7(x+2) < 3(2x+3)
Раскрываем скобки
{ 6x + 4 > 5x - 5
{ 7x + 14 < 6x + 9
Упрощаем
{ x > -9
{ x < -5
ответ: x = (-9; -5)
Пошаговое объяснение:
cos(x - 2Π) = sin(3Π - x)
По формулам приведения
cos(x - 2Π) = cos x
sin(3Π - x) = sin(Π - x) = sin x
Получаем
А) cos x = sin x
tg x = 1
x = Π/4 + Πk, k € Z
Б) В промежутке [-Π; Π/2] будут корни:
x1 = Π/4 - Π = -3Π/4; x2 = Π/4